Effect of Price, Quality, Trust on Repurchase Intentions (Case Study on PT Tokopedia) - Angel, Vivian; Pasaribu, Lamhot Henry (Jurnal Manajemen, 2022)
PT Tokopedia is an Indonesian technology company that specializes in e-commerce. This study aims to analyze the variables of price, quality, and trust on repurchase intentios and see whether the variables of price, quality and trust have a positive and significant influence on repurchase intentions. The research model is primary research where the researcher gets the price, quality, and trust variables from the survey results conducted by the researcher and repurchase intentions variable with the results of a discussion with one of the experts before the start of this study. The examination technique utilized is a quantitative exploration strategy with the kind of exploration as illustrative, theory testing, and correlational with a cross-sectional methodology. Respondents were chosen through likelihood inspecting and compounding examining. The quantity of respondents taken for this review is 607 respondents. The information for the aftereffects of this review were gotten through disseminating polls utilizing a Likert size of 1-5 utilizing Google Form. This review utilizes the PLS-SEM technique to examine the information. The aftereffects of this review show that value, quality, and trust affect repurchase aims. In light of the data acquired from the aftereffects of this review, Tokopedia can endeavor to keep up with costs, and enhancements of the quality and trust angles from Tokopedia clients by thinking about the segment part of most of Tokopedia clients.